Digital Transformation in Healthcare : Leveraging Technology to Enhance Patient Care - Sivasatyanarayanareddy Munnangi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the successful implementation of Pega’s Healthcare Customer Service and Care Management solutions at a major healthcare provider, demonstrating how digital transformation can revolutionize patient care delivery while optimizing operational efficiency. The implementation, which focused on integrated care coordination, patient case management, and compliance frameworks, resulted in significant improvements, including a 20% reduction in hospital readmissions, a 30% reduction in administrative costs, and a 25-35% reduction in operational costs. The organization achieved enhanced patient outcomes, streamlined operations, and improved regulatory compliance through comprehensive data integration, automated workflows, and user-centric design. The article highlights how strategic digital transformation initiatives, aligned with industry best practices and supported by robust change management, can successfully address healthcare’s complex challenges while positioning organizations for future innovation in care delivery.